Pengaruh Business Networking, Praktik Operasional Hijau, dan Akuntansi Digital terhadap Kinerja Perusahaan - Dian Widiyati; Neneng Hasanah (Universitas Pamulang, 2023)
This study aims to test and analyze how the influence of business networking, green operational practices, and digital accounting on company performance. The independent variables in this study are business networking, green operational practices, and digital accounting. While the dependent variable in this study is company performance. This research is quantitative research using primary data in the form of questionnaires. The population of this study is MSME actors in Jabodetabek. The sampling technique uses convenience sampling techniques so that a research sample of 105 respondents was obtained. The analysis tool used in this study is Smart-PLS. The results of this study are business networking has a positive effect on company performance, green operational practices have a positive effect on company performance and digital accounting has no effect on company performance.